Platelets in cancer - Mammadova-Bach, E.; Mangin, P.; Lanza, F.; Gachet, F. (Hämostaseologie, 2015)
Platelets are well-known for their major role in primary hemostasis and thrombosis. Cancer patients frequently manifest thrombotic events and present abnormalities in blood coagulation which appear to be linked to altered platelet function and turnover. Moreover, numerous studies indicate an intimate cross-talk between platelets and tumor growth, angiogenesis and metastatic dissemination. Finally, several experimental data and clinical trials suggest possible benefits of anti-platelet drugs on some cancers. Here, we will review the current state of basic biological research regarding the role of platelets in cancer progression. We also critically review the possible clinical applicability of some anti-platelet therapies to limit tumor growth and prevent metastatic dissemination.
Keywords: Platelet physiology; cancer; tumor metastasis; anti-platelet agents